Analysis of Technology Implementation In Public Services In The Field Of Education Quality at The Sidoarjo Dispendikkbud - Amelia, Dina Nur; Ilham (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
The application of information technology in public services is a strategic step in improving the efficiency and quality of services, including in the education sector. The Education and Culture Office of Sidoarjo Regency has implemented technology through APE MUDIK (Aplikasi Pelayanan Mutu Pendidikan), which is used internally by employees to support administrative services in the field of education quality. This study uses a qualitative descriptive approach to analyze how this technology is implemented and how it impacts the service process. Data collection techniques are carried out through interviews and observations of employees and interns involved in system operations. The results of the study indicate that APE MUDIK contributes to increasing employee work effectiveness and neatness of data management. However, this system cannot be used directly by the community and still faces technical obstacles such as network disruptions. From a Socio Informatics perspective, the use of APE MUDIK has changed work patterns and social interactions in the education bureaucracy environment.